Perbandingan pendekatan richard bell dan arthur jeffery dalam studi teks al-qur`an - Biari, Dina Audina Hasan (Maliki Interdisciplinary Journal, 2026)
Western scholarship on the Qur’an has developed significantly since the nineteenth century, particularly through the pioneering contributions of Ignaz Goldziher, who laid the foundation for historical-critical approaches to the study of Islamic scripture. In the modern era, Richard Bell and Arthur Jeffery emerged as two influential figures whose works left a lasting impact on Qur’anic textual criticism. This study examines and compares the approaches of these scholars as reflected in their major works, Materials for the History of the Text of the Qur’an and Introduction to the Qur’an. The analysis employs the framework of Orientalist Studies proposed by Sahiron Syamsuddin, which categorizes Orientalist approaches into three types: historical-critical, interpretative-exegetical, and descriptive anthropological-social. The findings demonstrate that although both Bell and Jeffery operate fundamentally within the historical-critical paradigm, their methodological emphases differ considerably. Jeffery focuses on textual and source criticism by documenting variant readings and early manuscript evidence, while Bell applies form and redaction criticism through attempts to reconstruct the chronological order of revelation. These differing approaches contribute substantially to Western Qur’anic studies but also evoke significant debate within Islamic scholarly tradition. The study aims to enrich understanding of modern Orientalist approaches to the Qur’an and highlights the need for further, more comprehensive comparative analyses in this field